2006
DOI: 10.3758/bf03193667
|View full text |Cite
|
Sign up to set email alerts
|

Putting phonetic context effects into context: A commentary on Fowler (2006)

Abstract: On the basis of a review of the literature and three new experiments, Fowler (2006) concludes that a contrast account for phonetic context effects is not tenable and is inferior to a gestural account. We believe that this conclusion is premature and that it is based on a restricted set of assumptions about a general perceptual account. Here, we briefly address the criticisms of Fowler (2006), with the intent of clarifying what a general auditory and learning approach to speech perception entails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 48 publications
0
71
1
Order By: Relevance
“…These accounts generally concentrate on variation that is created by continuous speech processes-that is, coarticulation. Again, different mechanisms have been proposed, ranging from the recovery of speech gestures from the signal (Fowler, 1996;Liberman, 1996), to general auditory mechanisms (Lotto & Holt, 2006;, to more abstract pattern recognition mechanisms (Smits, 2001). An example of the latter is the phonological-inference account of Gaskell and Marslen-Wilson (1998), in which phonological rules rectify the variant forms into the canonical form.…”
Section: Discussionmentioning
confidence: 99%
“…These accounts generally concentrate on variation that is created by continuous speech processes-that is, coarticulation. Again, different mechanisms have been proposed, ranging from the recovery of speech gestures from the signal (Fowler, 1996;Liberman, 1996), to general auditory mechanisms (Lotto & Holt, 2006;, to more abstract pattern recognition mechanisms (Smits, 2001). An example of the latter is the phonological-inference account of Gaskell and Marslen-Wilson (1998), in which phonological rules rectify the variant forms into the canonical form.…”
Section: Discussionmentioning
confidence: 99%
“…When nonspeech sine wave tone contexts with spectra modeling the third-formant ͑F3͒ offset frequency of /al/ and /ar/ precede /ga/ to /da/ targets, context-dependent speech categorization shifts are observed that mirror the effects produced by /al/ and /ar/ speech contexts. Other studies have verified the generality of this finding ͑for a brief review, see Lotto and Holt, 2006͒. Nonspeech context effects on speech categorization have been observed with nonspeech analogs of consonant contexts affecting categorization of consonants ͑Fowler et al, 2000;Lotto et al, 2003;vowels ͑Holt et al, 2000͒.…”
Section: Introductionmentioning
confidence: 74%
“…Such accounts assume that only canonical forms are stored in the lexicon and that listeners learn how to map variant forms onto stored canonical forms through exposure (e.g., Gaskell & Marslen-Wilson, 1998;Lotto & Holt, 2006;. These models thus also make assumptions about representations, but the burden of their explanation for recognition of variant forms is carried by their assumptions about processing.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in two subsequent experiments, we examined how short-term training on an accent influences word recognition, again as a function of strength of accent (Experiment 2), but also as a function of speaker (Experiment 3). The results of these experiments will be related to models of spoken-word recognition and the accounts they offer for how listeners cope with pronunciation variation-those based on representation (e.g., Goldinger, 1998;Johnson, 2006;Pierrehumbert, 2001;Ranbom & Connine, 2007) and those based on processing (e.g., Gaskell & Marslen-Wilson, 1998;Lotto & Holt, 2006;Mitterer, Csépe, Honbolygo, & Blomert, 2006).…”
Section: Familiarity With German-accented Dutchmentioning
confidence: 99%